Pengaruh Citra Merek Dan Persepsi Harga Terhadap Kepuasan Pelanggan Melalui Keputusan Pembelian Di Richeese Factory Kemang Jakarta Selatan - Ramdhani, Bagas; MH Nainggolan, Bonifasius (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2022)
The analysis of this study aims to identify the Influence of Brand Image and Price Perception on Customer Satisfaction through Purchasing Decisions at Richeese Factory Kemang South Jakarta PLS-SEM to process data. Purposive sampling was used in sampling techniques with 200 respondents. The results of hypothesis testing show that there is a positive and significant impact between brand image and price perception between customer heat and purchasing decisions ultimately overall have a positive and significant impact between The Influence of Brand Image and Price Perception On Customer Satisfaction Through Purchasing Decisions. So, Recheese Factory Kemang South Jakarta can continue to maintain the brand image to better lag and maintain affordability so that customers can think positively about the price set by the company. Therefore, brand image and price perception are important factors to maximize customer satisfaction and delivery decisions.